Hydrogel - based green wall - Oh, Jun Xian (Nanyang Technological University, 2022)
In recent years, green infrastructure represents an emerging field in technology and research. At present, the vertical greening systems have gained considerable interest and adoption towards sustainable approaches. These systems have been incorporated in building design elements to facilitate urban adaptation to a warm climate, reduce surface temperatures and mitigate energy consumption of a building. Apart from its benefits for the environment, it is also visually appealing and promotes healthier air quality. However, the implementation of a vertical greening system can largely be demotivated by the significant installation and maintenance costs. To address these issues, this study seeks to develop a cost-efficient modular green wall (Chapter 8). On top of designing a modular green wall, we seek to evaluate the effectiveness of hydrogels as a growing medium, on the growth and survivability of the plants over several weeks (Chapter 7). Majority of the plants in this experiment that were transplanted onto hydrogels did not display any signs of observable growth and eventually withered away. Several factors could have led to these observations, such as an uneven water distribution within the hydrogel, lack of sunlight, and the lack of air within the hydrogel. The hydrogel also does not possess any form of nutrients, which are essential for plants survivability. The hydrogel was ultimately not a suitable growing medium. On the other hand, the modular green wall was able to support the weight of the growing medium and plants. The irrigation durations of both the water and liquid fertiliser were designed to be irrigated at specific intervals, allowing for an automated modular green wall system. Together with these features, the construction of the modular green wall provided remarkable structural support for the growing medium and plants.